(untitled) (Annual of the Faculty of Philosophy in Skopje, 2019)
The social life of man is complex and deeply rooted in his personality. The ability to cooperate, to lead, to follow, to negotiate and to care for the other makes the human being what it is. Yet, how exactly we manage to coordinate, understand others’ states and intentions and signal our own, still needs clarification. Taking into account the nature of empathy as a potential psychological motivator for helping others in distress, it is logical to consider it a key factor in people’s social life. This study talks about empathy in children and youth as an ability that develops and is learned, but it also has genetic origin. However, the main goal is to examine empathy and its connection with the sociality of children and adolescents. In this direction firstly it will be described the nature of empathy and all factors that influence its creation and development, and then we will associate it with the behaveour of child and adolescent with their peers, that is, with sociality. All findings are based on scientific research and theories in this field.